Chromatin Immunoprecipitation in Early Xenopus Laevis Embryos - Blythe, Shelby A. (2009)
Chromatin immunoprecipitation (ChIP) is a powerful method for analyzing the interaction of regulatory proteins with genomic loci, but has been difficult to apply to studies on early embryos due to the limiting amount of genomic material in these samples. Here, we present a comprehensive technique for performing ChIP on blastula and gastrula stage Xenopus embryos. We also describe methods for optimizing crosslinking and chromatin shearing, verifying antibody specificity, maximizing PCR sensitivity, and quantifying PCR results, allowing for the use of as few as 50 early blastula stage embryos (approximately 5×10(4) cells) per experimental condition. Finally, we demonstrate the predicted binding of endogenous β-catenin to the nodal-related 6 promoter, binding of tagged Fast-1/FoxH1 to the goosecoid promoter, and binding of tagged Tcf3 to the siamois and nodal-related 6 promoters as examples of the potential application of ChIP to embryological investigations.